Volatile accretion history of the Earth. - Wood,BJ; Halliday,AN; Rehkämper,M (Nature, 2010)
It has long been thought that the Earth had a protracted and complex history of volatile accretion and loss. Albarède paints a different picture, proposing that the Earth first formed as a dry planet which, like the Moon, was devoid of volatile constituents. He suggests that the Earth's complement of volatile elements was only established later, by the addition of a small veneer of volatile-rich material at ∼100 Myr (here and elsewhere, ages are relative to the origin of the Solar System). Here we argue that the Earth's mass balance of moderately volatile elements is inconsistent with Albarède's hypothesis but is well explained by the standard model of accretion from partially volatile-depleted material, accompanied by core formation.